Environmentally relevant concentrations of microplastics and phenanthrene show limited effects on the behaviour and physiology of green crab lineages - Lorenzo Cozzolino; Katy R. Nicastro; Christopher D. McQuaid; Halldór P. Halldórsson; Fernando P. Lima; Gerardo I. Zardi (Ecotoxicology and Environmental Safety)
Plastic pollution is a growing environmental concern, with microplastics (MPs) and associated contaminants such as polycyclic aromatic hydrocarbons (PAHs) jeopardising the resilience and long-term survival of marine species. While species-specific effects have been well-documented, the role of intraspecific diversity in modulating species' responses to these contaminants remains largely neglected. This study investigates whether genetically distinct lineages of the green crab (Carcinus maenas) differ in their behavioural and physiological responses to environmentally relevant concentrations of polyethylene microplastics (PE) and PE contaminated with phenanthrene (PE+PHE). Juvenile crabs from the Southwest European (SWE) and Icelandic (ICE) populations were exposed to control seawater, PE, or PE+PHE for 72 h, and their behavioural (i.e., food contest) and physiological performances (i.e., heart rate) were assessed. Overall, there were no significant effects of PE or PE+PHE on key behavioural traits related to food competition (e.g., latency to initiate movement, interbout intervals, contest outcome) or on physiological parameters such as heart rate. However, resource possession was significantly reduced in ICE crabs exposed to PE. Our findings suggest that C. maenas exhibits short-term resilience to MPs and PAHs, with similar behavioural responses across distinct genotypic lineages (SWE = ICE). However, differences in heart rates between genetically distinct populations, even in control conditions, highlight the potential effect of lineage-specific physiological plasticity. In addition, high inter-individual variability in behavioural responses suggests susceptibility to MPs and PAHs may not be uniform within populations. Long-term assessments incorporating individual-based analyses are needed to fully understand the complex interplay between plastic pollution, genetic diversity, and behavioural plasticity in this marine species.